Five main processes in healthcare: a citizen perspective. (30th March 2011) - Bergman, Bo; Neuhauser, Duncan; Provost, Lloyd
Abstract : A citizen point of view on the healthcare system, its processes and their improvement is emphasised. From this point of view, five main processes are identified: Keeping Healthy, Detecting Health Problems, Diagnosing Diseases, Treating Diseases and Providing for a Good End of Life. The citizen should be looked upon as a cocreator of value and improvement of these processes.